2023
DOI: 10.1002/advs.202207693
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Receptor‐Mediated Iron Uptake Promotes Colon Tumorigenesis

Abstract: Transferrin receptor (TFRC) is the major mediator for iron entry into a cell. Under excessive iron conditions, TFRC is expected to be reduced to lower iron uptake and toxicity. However, the mechanism whereby TFRC expression is maintained at high levels in iron-enriched cancer cells and the contribution of TFRC to cancer development are enigmatic. Here the work shows TFRC is induced by adenomatous polyposis coli (APC) gene loss-driven 𝜷-catenin activation in colorectal cancer, whereas TFRC-mediated intratumora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Here, we determined that LASS2 interacts with TFRC in these specific cancer cell types. TFRC, also known as transmembrane glycoprotein transferrin receptor 1 (TFR1), is the predominant iron uptake protein on cell membranes; it regulates intracellular iron levels and plays a crucial role in maintaining iron homeostasis and ferroptosis [ 28 , 37 , 38 ]. Iron plays a pivotal role in cell viability and requires precise control of cellular iron homeostasis, including intracellular iron storage/release and import/export [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we determined that LASS2 interacts with TFRC in these specific cancer cell types. TFRC, also known as transmembrane glycoprotein transferrin receptor 1 (TFR1), is the predominant iron uptake protein on cell membranes; it regulates intracellular iron levels and plays a crucial role in maintaining iron homeostasis and ferroptosis [ 28 , 37 , 38 ]. Iron plays a pivotal role in cell viability and requires precise control of cellular iron homeostasis, including intracellular iron storage/release and import/export [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of ZEB2 in HIF3A1 overexpressing cells with small interfering RNA results in decreased migratory capacity as well as increased expression of epithelial cell markers. Recently we have reported that TFRC is critical for colon tumorigenesis 21 . Here we report that HIF-3α1 increases the expression of an iron importer TFRC, iron levels within cells, and that iron chelation reduces cancer cell survival as well as reduces the protein levels of mesenchymal markers.…”
Section: Discussionmentioning
confidence: 99%
“…Staining was performed as we described before 21 . Cells were plated at a concentration of 1 ×10 4 cells/mL in a 96-well plate.…”
Section: Histology Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is also study claimed that TfR1 mRNA and protein levels in colon cancer tissue are significantly higher (53). TFRC is induced by adenomatous polyposis coli (APC) gene loss-driven b-catenin activation in CRC, iron chelation, and TFRC disruption increase DNA replication stress, DNA damage response, apoptosis, and reduce colon tumor growth (54). Decreased expression of MiR-107 in colon cancer tissue prevented the proliferation, migration, and infiltration of CRC cell SW620 by inhibiting TfR1 expression (55).…”
Section: Transferrin Receptormentioning
confidence: 99%